Conceptual graph formalism for financial text representation - Kamaruddin, Siti Sakira; Abu Bakar, Azuraliza; Hamdan, Abdul Razak; Mat Nor, Fauzias (2008)
We present an approach to automatically transform a financial text into conceptual graph formalism.The approach exploits the constituent structure of sentences and general English grammar rules to perform the transformation.We suggest face validation and traces as the evaluation method to be performed on the resulting formalism to validate its accuracy. We also discuss the potential manipulation and application of the constructed conceptual graph database.